Distribution of Elements in Some Aridisols Developed on Quaternary Sediments - Choudhari, J S (Annals of Arid Zone, 2016)
Seven pedons of Aridisols, developed on aeolian an<1 alluvial plains, and formed during early Holocene to early Pleistocene in western Rajasthan were studied for the total elemental composition, their distribution and :association of elements with each other and also with soil constituents. Results showed that Si was the most predominant element followed by Al, Fe, Ca, Mg. Na, K, Mn, Zn and Cu. The content of AI, Fe, Mg, Cu and Zo was found 10 increase in soils with increasing age of the landforms. The Aridisols developed on older landforms showed a higher concentration of Fe, Al, Mn, Mg, Cu and Zn in the B horizon of the profiles than A and C horizon, wheleas these were uniformly distributed in soils developed on Holocene aged landforms. Correlation matrices revealed a variance control of finer fraction on the content of Al, Fe, Mg, and K.